STUDY ON NEW TRENDS IN DRUG DELIVERY SYSTEMS - Neeta T Gavimath; Pavan Kumar K (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Drug delivery science has advanced far beyond conventional tablets and injections, introducing innovative technologies that enhance therapeutic precision, patient comfort, and safety. Objective: To evaluate the awareness, perception, and adoption of emerging drug delivery technologies amongparticipants, including healthcare professionals, pharmacists, and patients.Methodology: This descriptive cross-sectional study was conducted at Navodaya Medical College Raichur, India. Data were collected using a pretested structured questionnaire assessing knowledge, attitudes, and usage patterns of advanced delivery systems such as nanocarriers, transdermal patches, microneedles, and implantable devices.Results: Among 255 participants, 55.7% were female and 49.8% held a university-level education. Awareness was highest for transdermal (82.0%) and inhalation systems (87.5%), while only 46.3% were aware of implantable or controlled-release systems. Most respondents (83.1%) agreed that new drug delivery technologies improve treatment precision, and 77.6% believed they reduce side effects. However, 65.5% perceived them as expensive, and only 38.8% felt adequately trained to use them. Adoption was higher for transdermal and inhalation systems, while microneedle and implantable devices showed limited usage.Conclusion: It is concluded that awareness and acceptance of advanced drug delivery systems are increasing, but their clinical application remains restricted by cost, limited training, and insufficient availability.